The Source Text of Opera Surtitles - Virkkunen, Riitta (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractThis article discusses the source text and reading situation of opera surtitles. It introduces opera from a multimodal viewpoint and differentiates between the dramatic text and the stage interpretation. With two versions of surtitles, it approaches two different surtitling strategies, the one that concentrates on the libretto and the other that focusses on the particular stage interpretation. As a result, the article asks if we should consider the stage interpretation to be the only appropriate source text of surtitles.